Chemoselective Synthesis of Dithioacetals from Bio‐aldehydes with Zeolites under Ambient and Solvent‐free Conditions. Issue 6 (22nd February 2017) - Li, Hu; Yang, Tingting; Riisager, Anders; Saravanamurugan, Shunmugavel; Yang, Song
Abstract: Dithioacetals are an important class of versatile compounds extensively applied in pharmaceuticals, separations, electrochemistry, and organic synthesis, but few heterogeneous catalytic systems are reported to be generally applicable for their synthesis from a wide range of substrates. A series of commercial and modified zeolites are excellent catalysts for thioacetalization of different thiols with carbonyl compounds, including biomass‐derived aldehydes, at room temperature under solvent‐free conditions. A near quantitative yield of dithioacetal was obtained over H‐beta(19) at room temperature with a low catalyst to substrate ratio of 1:19, and a method to follow the reaction progress by ex situ UV/Vis absorption analysis was demonstrated. Recycling experiments with H‐beta(19) in five consecutive runs resulted in slight loss of activity, but the original activity could be fully restored after calcination at 550 °C. The results and physicochemical properties of the zeolites revealed that relatively large pores and moderate acidity with an appropriate distribution of Brønsted/Lewis acid sites contributed to the pronounced performance in the dithioacetal formation. Abstract : Benign biorefinery route : Various value‐added dithioacetals are catalytically synthesized in near quantitative yields from solvent‐free thioacetalization of biomass‐derived aldehydes at room temperature. The pronounced performance is obtained with large‐pore zeolites with moderate acidity and an appropriate distribution of Brønsted/Lewis acid sites.